Change Concepts and Innovation. - Glor, Eleanor D. (Innovation Journal, 2025)
Discussions of public service innovation and change tend to bandy about complex concepts derived from the fields of organizational psychology, sociology and management. This paper moves away from the "one best way" approach to describe some of the relevant concepts and possible differences between change and innovation. Some governments, among them the Government of Canada (GoC) and international organizations (OECD), now specify innovation as an objective. The Canadian Clerk of the Privy Council, for example, in her Fourth Annual Report to the Prime Minister said that "experimentation and innovation need to be encouraged and supported" Bourgon, 1997: 26). In her Fifth Annual Report she said "The Canadian model ... encourages experimentation and the emergence of a diversity of institutional models to put before decision makers" (Bourgon, 1998: 1). Although what is meant by the term innovation is not always totally clear, and it often merely means improvements, institutional support for "innovation" is now more common. Often this is symbolic support for the current ideology. This paper explores some of the major factors that have affected government's capacity to be innovative, including paradigms followed, definitions used or implied, the approach to organizational change, motivation to innovate, organizational capacity for change, change management, discourses and people, organizational culture, the politics of change and impact. A wide range of literature was consulted in Google Scholar.